The Effect of Cognitive Motor Dual Task-Based Exercise Game Therapy on the Quality of Life and Endurance in the Elderly - Andika Andika; Hilmi Zadah Faidullah; Riska Risty Wardhani (Journal of Social Research, 2026)
Imprisonment at an advanced age impairs physical, mental, and social well-being, declining quality of life for elderly Correctional Assisted Citizens (Warga Binaan Pemasyarakatan/WBP) at Class IIB Sleman Prison. The PKM-PM team from ‘Aisyiyah University of Yogyakarta implemented a Cognitive Motor Dual Task (CMDT) program based on Exercise Game Therapy (EGT) to realize Urip Apik (good quality of life) via interactive physical-cognitive exercises. Conducted July 4–October 19, 2025, it involved 12 elderly WBPs, supported by health workers and officers. The program featured three stages: Apik Raga (physical coordination), Apik Rasa (cognitive-emotional well-being), and Apik Rengkuh (social confidence). Activities included discussions, assessments, interventions, and SF-36 evaluations, boosting average quality-of-life scores from 52.1 to 72.6 (39.35% improvement), especially in social functioning, emotional well-being, and energy. Internal questionnaires showed knowledge rising from 39.6% to 87.5% and skills from 64.6% to 89.6%, with gains in self-acceptance, motivation, and interaction. It aligns with Permenkumham No. 32/2018, Law No. 39/1999 on Human Rights, SDGs 3 and 10, and Asta Cita priorities for vulnerable groups.